2019
DOI: 10.1016/j.compositesb.2019.107052
|View full text |Cite
|
Sign up to set email alerts
|

Effective behavior of composites with combined kinematic and isotropic hardening based on additive tangent Mori–Tanaka scheme

Abstract: The goal of the present work is to propose a multi-scale approach for composite materials which accounts for kinematic hardening in the phases. For that purpose, the additive/sequential interaction rule and tangent linearization of viscoplastic response proposed for elastic-viscoplastic material can be extended in a straigthforward manner. A two phase composite where each phase is elastic-viscoplastic is considered. The viscoplastic flow is governed by a J 2 flow theory with an overstress. To find the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…The plastic multiplier Γ is then computed, as in the case in which the residual is considered, by means of a Newton-Raphson algorithm, with the derivatives following from Equations ( 43)- (45) without the residual stress. The updated expressions when neglecting the residual stress of…”
Section: Radial Return Mapping Neglecting the Residual Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The plastic multiplier Γ is then computed, as in the case in which the residual is considered, by means of a Newton-Raphson algorithm, with the derivatives following from Equations ( 43)- (45) without the residual stress. The updated expressions when neglecting the residual stress of…”
Section: Radial Return Mapping Neglecting the Residual Stressmentioning
confidence: 99%
“…The direct linearization approach for the definition of the LCC is used in the secant formulation by Berveiller and Zaoui, 36 Tandon and Weng 37 and so forth, a formulation which allows representing visco-plastic behaviors under proportional and monotonic loading conditions. Other approaches are the affine formulation [38][39][40] and so forth, which is valid for arbitrary loading history of visco-plastic models, the incrementally affine formulation, 41,42 or the incremental-tangent formulation, 19,[43][44][45] and so forth, which allow representing arbitrary loading. There is one main drawback when using the affine, incrementally-affine and incremental-tangent formulations, which is the anisotropicity of their tangent operators.…”
Section: Introductionmentioning
confidence: 99%
“…By the definition of the tangent compliance tensor, the slip system backstress has been treated as an internal variable independent of the stress state, similarly to the recent development of the additive interaction law combined with the Mori-Tanaka scheme for two-phase composite materials presented in Mercier et al (2019).…”
Section: Constitutive Relation For the Single Crystalmentioning
confidence: 99%
“…Moreover it is clear that for cyclic loading, Bauschinger effect is present. Therefore a Mori-Tanaka scheme for two-phase materials with kinematic hardening was recently developed in Mercier et al (2019) and compared well with finite element predictions. It was shown that the additive tangent interaction law is capable to manage kinematic hardening with good efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Three spatial limit hexagons of plasticity 1-2, 2-3 and 1-3 as the intersections of the limit prism of plasticity and three coordinate planes are also marked in Figure 3 . The axis of the respective area is identical to the so-called hydrostatic axis which passes through the origin of the coordinate system and is equidistant from all three major axes [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: An Analytical Description Of Elastic–plastic Materials Behmentioning
confidence: 99%